Nível de atividade física, perfil de saúde e fatores de risco para doenças crônicas em servidores de um hospital escola do sul do Brasil - Ieker, Ana Silvia Degasperi (2017)
This dissertation adopted the alternative model (Scandinavian) in the formulation of two objectives: a) to determine the exposure of health workers to behaviors and risk factors for the development of chronic non-communicable diseases; B) to associate the self-reported barriers to the practice of physical activity and behavior change in servers. A cross-sectional survey was carried out from October to December 2016. The population was composed of 485 effective employees of a School Hospital of Southern Brazil, aged 22 to 66 years. The research was carried out in the workplace of each server, in the form of interviews (junction of validated questionnaires), anthropometric evaluation (weight, height, waist circumference) and blood pressure measurement. Only those who agreed to participate in the study and who signed the Free and Informed Consent Form were evaluated. The variables analyzed were: physical activity level, body mass index, waist circumference, blood pressure, age range, smoking, alcohol consumption, hours of sleep, stage of behavior change and barriers to the practice of physical activity. This work was approved by the ethics committee in researches with human beings of the State University of Maringá. Men presented higher prevalences of overweight / obesity and high abdominal circunference, respectively 74.4% and 51.7%. When adjusted for age, there was a significant association between overweight / obesity (p = 0.005) and abdominal circumference (p = 0.027). The highest prevalence of risk conditions is in the age group of 40 to 50 years, remaining in the course of the age. When considered the gender-adjusted analysis, the general population aged 50 years or older was 2.2 times more likely to have high waist circumference and 2.5 times more likely to have a high BMI (CI (1.1 - 4.5 ) P = 0.025 and IC (1.5 - 4.3) p = 0.001). The evaluation of the perceived barriers to the practice of physical activity affirmed laziness (44.1%), lack of free time (63.1%) and lack of companionship (34.1%) as the main reasons that hinder or hinder individuals Engage in the practice of activities. The men in this study had a significant difference between inactive and active behaviors in the barriers: not liking AF (p = 0.018), injury (p = 0.003) and company (p = 0.005). Among women, there was a significant difference only in the barrier fear of injury (p = 0.002). Concern levels of physical inactivity were observed in all age groups, this is a warning for strategies to promote physical activity from the hiring of these servers and points out the need to value the hours spent working as effective strategies for health promotion.